2020
DOI: 10.3389/fbuil.2020.558034
|View full text |Cite
|
Sign up to set email alerts
|

Formalizing Tag-Based Metadata With the Brick Ontology

Abstract: Current efforts establishing semantic metadata standards for the built environment span academia, industry and standards bodies. For these standards to be effective, they must be clearly defined and easily extensible, encourage consistency in their usage, and integrate cleanly with existing industrial standards, such as BACnet. There is a natural tension between informal tag-based systems that rely upon idiom and convention for meaning, and formal ontologies amenable to automated tooling. We present a qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Fourteen different schemas have been identified that describe metadata about controls and metering in commercial buildings, but from this high-level review, the overlaps between them and their gaps are unclear. An extensive comparison between Brick and Project Haystack is presented in [148], but no publication compares all these schemas in depth. Gilani et al tried to evaluate the scope of several ontologies by identifying what type of data they describe (e.g., external conditions, energy use), but these categories are too broad to clearly identify the differences between schemas.…”
Section: The Landscape Of Metadata Schemas For Building Energy Applicmentioning
confidence: 99%
“…Fourteen different schemas have been identified that describe metadata about controls and metering in commercial buildings, but from this high-level review, the overlaps between them and their gaps are unclear. An extensive comparison between Brick and Project Haystack is presented in [148], but no publication compares all these schemas in depth. Gilani et al tried to evaluate the scope of several ontologies by identifying what type of data they describe (e.g., external conditions, energy use), but these categories are too broad to clearly identify the differences between schemas.…”
Section: The Landscape Of Metadata Schemas For Building Energy Applicmentioning
confidence: 99%
“…Brick, conversely, is a more structured, formal, and expressive ontology, but it requires more specialized software tools, and it is still under development. A more formal comparison of the two schemas is presented by Fierro et al [75].…”
Section: Table 2 Summary Of the Selected Data Tools: Unique Features mentioning
confidence: 99%
“…In addition to development in occupant-centric metrics and occupancy sensing technologies, there has been significant advancement in the standardized representation of operational building data [27][28][29]. Many different forms of digital information are produced over the lifespan of a building, capturing design, construction, commissioning, operations and controls, maintenance, and audit information.…”
Section: Developments In Data Schemas For Buildingsmentioning
confidence: 99%
“…Until recently, neither the schema nor accompanying documentation were provided in a machine readable format. The newest version, Haystack 4 (currently in prerelease), has addressed this while also defining concepts in a taxonomic structure to address some previous critiques [28]. The Brick Schema was developed to provide a more formalized class hierarchy than Haystack 3 originally implemented.…”
Section: Developments In Data Schemas For Buildingsmentioning
confidence: 99%
See 1 more Smart Citation